SBBS Program - African Naming Ceremony - SJSU Striving Black Brothers and Sisters::::::::::::::: (2024)
Program for the 3rd Annual African Naming Ceremony, presented by Striving Black Brothers and Sisters and funded by Associated Students. Held on February 1, 1995 at 7:00 PM. The event included speakers, poetry, singing, and African drumming.